2018
DOI: 10.1073/pnas.1719601115
|View full text |Cite
|
Sign up to set email alerts
|

Microglia inhibit photoreceptor cell death and regulate immune cell infiltration in response to retinal detachment

Abstract: SignificancePhotoreceptor cell death resulting from retinal detachment (RD) causes significant visual loss. While the immune system is activated during RD, its role is still unclear. Microglia are resident immune cells in the retina and are thought to be either protective or deleterious in response to neuronal injury, suggesting context-dependent effects. Here, we demonstrate that microglia limit retinal damage during acute injury, since microglial ablation led to increased photoreceptor death. Microglial morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
108
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 71 publications
(110 reference statements)
12
108
1
1
Order By: Relevance
“…S4). These structures are similar to ones discovered as a result of photoreceptor degeneration after retinal detachment (Okunuki et al, 2018). There is increasing evidence that relates deficits in extracellular matrix with degenerative disorders like macular degeneration (Al-Ubaidi, Naash et al, 2013, Fernandez-Godino, Pierce et al, 2016.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…S4). These structures are similar to ones discovered as a result of photoreceptor degeneration after retinal detachment (Okunuki et al, 2018). There is increasing evidence that relates deficits in extracellular matrix with degenerative disorders like macular degeneration (Al-Ubaidi, Naash et al, 2013, Fernandez-Godino, Pierce et al, 2016.…”
Section: Discussionsupporting
confidence: 73%
“…In healthy retinas, microglial cells (Iba1+) displayed a ramified morphology, and are located specifically in the ganglion cell, and inner and outer plexiform layer (SI Appendix Fig. S3), as previously reported (Okunuki, Mukai et al, 2018). Interestingly, in IMPG2 KO mice we observed Iba1-positive cells invading the photoreceptor layers and the subretinal lesions ( Fig.…”
Section: Subretinal Lesions Are Rich In Impg1 Proteoglycan and Activasupporting
confidence: 83%
“…Degenerated photoreceptors are eliminated in the absence of microglia/macrophage infiltration. Previous studies have reported that degenerated photoreceptors are eliminated by professional phagocytes such as microglia and macrophages [15][16][17][18][19][20] . Therefore, we conducted immunofluorescence for Iba1, a microglia/macrophage marker, in combination with TdT-mediated dUTP nick end labeling (TUNEL) assay to assess whether degenerated photoreceptors were eliminated by microglia/macrophages (hereafter referred to collectively as macrophages) also in our retinal injury model.…”
Section: Resultsmentioning
confidence: 99%
“…There is controversy as to which cell type or types are predominantly involved in the phagocytic removal of degenerated cells in the retina. While many studies have suggested the primary role of professional phagocytes such as microglia or bone marrow-derived macrophages [15][16][17][18][19][20] , other cell types such as Müller glia are also reported to show phagocytic activity during development 34,35 or under pathological conditions [22][23][24][25] . A recent report has further suggested that Müller glia play a predominant phagocytic role during the early stage of photoreceptor degeneration in RhoP23H/P23H mice 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Microglia have been shown to accelerate degeneration by phagocytosing stressed but still living photoreceptors in a process termed phagoptosis (56); inhibition of this form of phagocytosis in the rd10 model by the blockade of the vitronectin receptor resulted in slowed degeneration (6), while its augmentation in CX3CR1 deficiency accelerated loss of photoreceptor structure and function (11). Conversely, in a model of retinal detachment, retinal microglia appear to support photoreceptor survival; when autofluorescent microglia, which presumably had phagocytosed photoreceptors, were pharmacologically depleted, degeneration was increased (57). We discover here in the rd10 retina that both C3 and CR3 participate in facilitating microglial phagocytosis of apoptotic photoreceptors; when either of these factors are deficient, decreased microglial phagocytosis was accompanied by increased accumulation of apoptotic cells, increased proinflammatory cytokine expression, and accelerated degeneration.…”
Section: Discussionmentioning
confidence: 99%